Pengaruh Transformational Leadership terhadap Financial Performance dengan Supply Chain Integration dan Job Satisfaction sebagai Variabel Intervening: Studi kasus pada Perusahaan Manufaktur yang go public di Surabaya dan Sidoarjo - Philipe Tiono (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of transformational leadership to job satisfaction, supply chain integration to financial performance, job satisfaction to financial performance, on go public manufacturing firms in Surabaya and Sidoarjo. This study used quantitative approach, and the data obtained through the distribution of questionnaire and used ratio financial statement analysis to go public manufacturing firms in Surabaya and processed by using SmartPLS software. This study showed that there was a positive and significant relationship of transformational leadership to financial performance, transformational leadership to job satisfaction, transformational leadership to supply chain integration, and supply chain integration to financial performance on go public manufacturing firms in Surabaya and Sidoarjo Job satisfaction and supply chain integration became the intervening variables to transformational leadership and financial performance.